Characterization of Macroscopic Fungi on Leaf Litter in Harau Valley, West Sumatra - Atika Melwisra; Fitratul Aini (DIVERSITAS HAYATI, 2023)
Fungi are one of the many types of organisms that play an important role in maintaining the balance and nature of nature. As a tropical country with vast rainforests with a high diversity of macroscopic fungi, biodiversity is an important aspect that supports living systems on earth and maintains the sustainability and evolution of ecosystems. Fungal communities, especially saprophytic fungi, are often neglected in biodiversity inventories in the Harau Valley Area of West Sumatra